THE INFLUENCE OF MANAGEMENT ASSURANCE AND ACCOUNTING INFORMATION SYSTEMS ON MANAGERIAL PERFORMANCE - Hadiyat, Yana; Arsjah , Regina (JRAK, 2024)
Managerial performance can be an added value in increasing achievements in management. The research aims at determining empirical evidence of the influence of organizational commitment, and management accounting information system characteristics on managerial performance which was moderated by the success of implementing the accounting information system. The type of data used was primary data and the population was collected from West Java BUMN employees. This research found that Digital Skills and Aggregated had a high influence on Managerial Performance. The research implied that the implementation of government accounting standards and good-quality financial reports could increase the accountability of government agency performance.